Utilizing hippocratic database for personal information privacy protection - Mohamed Sidek, Zailani (Penerbit UTM Press, 2008)
In today's digital world, privacy protection over personal information has become a major element in web based application. Both parties involved in a web based application transaction, either consumer or application provider should be ensured with this privacy. Protecting privacy are always related with personal information. Personal information is an information type that usually needs to keep as a private. Because of the important of privacy concerns today, we need to design a database system that suits with privacy. Agrawal et. al. has introduced Hippocratic Database. This paper will explain how HOB can be a future trend for web-based application to enhance their privacy level of trustworthiness among internet users